The effect of low-volume high-intensity interval training on cardiovascular health outcomes in type 2 diabetes: A randomised controlled trial. (1st December 2020) - Way, Kimberley L.; Sabag, Angelo; Sultana, Rachelle N.; Baker, Michael K.; Keating, Shelley E.; Lanting, Sean; Gerofi, James; Chuter, Vivienne H.; Caterson, Ian D.; Twigg, Stephen M.; Johnson, Nathan A.
Abstract: Background: Low-volume high-intensity interval training (HIIT) may be a time-efficient strategy that leads to similar or superior improvements in cardiorespiratory fitness (CRF) and cardiovascular disease (CVD) risk factors when compared with moderate-intensity continuous training (MICT). Our study investigated the effect of low-volume HIIT or MICT versus sham placebo-control (PLA) on central arterial stiffness, hemodynamic responses, and CVD risk factors in adults with obesity and type 2 diabetes (T2D). Methods: Eligible participants were previously inactive adults with obesity and T2D. Individuals were randomly allocated to: i) HIIT (1 × 4 min cycling at 90% peak oxygen consumption [V̇O2peak ]); ii) MICT (45 min of cycling at 60% VO2peak ); or PLA. Training groups exercised thrice weekly for 12 weeks. Central arterial stiffness, hemodynamics and CVD risk factors were assessed at baseline and post-intervention. Analysis of covariance (ANCOVA) was used to examine changes following HIIT, MICT and PLA. Results: Thirty-five participants (age: 55.1 ± 1.4 years, BMI: 36.1 ± 0.8 kg/m 2 ) completed the study. A significant intervention effect was found for changes in pulse wave velocity (PWV) ( p = .03), which reduced with HIIT (−0.3 ± 0.9 m/s) and MICT (−0.1 ± 1.1 m/s) but increased with PLA (0.8 ± 1.6 m/s). There was a significant intervention effect for changes in V̇O2peak ( p < .01), glycosylated hemoglobin ( p = .03), systolic blood pressure (p < .01), and waist circumference (p = .03), which all improved following MICT or HIIT but not PLA; there was no difference between MICT and HIIT. Conclusions: Twelve minutes of low-volume HIIT per week leads to improvements in central arterial stiffness and cardiovascular health in inactive individuals with obesity and T2D. Highlights: Cardiovascular disease is the leading cause of mortality in people with type 2 diabetes. "Lack of time" is a commonly cited as a barrier to participating in exercise in such individuals. Just 12 min of low-volume HIIT per week can significantly reduce central arterial stiffness and improve cardiovascular health outcomes in adults with type 2 diabetes. Low-volume HIIT provides a time-efficient exercise approach for reducing the cardiovascular burden in this population.